2022
DOI: 10.1111/liv.15222
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized carbon 13 MRI in liver diseases: Recent advances and future opportunities

Abstract: Hyperpolarized carbon‐13 magnetic resonance imaging (HP 13C MRI) is a recently translated metabolic imaging technique. With dissolution dynamic nuclear polarization (d‐DNP), more than 10 000‐fold signal enhancement can be readily reached, making it possible to visualize real‐time metabolism and specific substrate‐to‐metabolite conversions in the liver after injecting carbon‐13 labelled probes. Increasing evidence suggests that HP 13C MRI is a potential tool in detecting liver abnormalities, predicting disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
(230 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, the HP [1- 13 C] pyruvate MRSI study after 2 months of treatment with taxane + platinum chemotherapy showed the efficacy of treatment with a reduced k PL value of 0.015 (s −1 ). This clinical study supports the feasibility of HP [1- 13 C] pyruvate MRSI in future clinical studies of metastatic cancer [ 62 , 63 ].…”
Section: Liver Cancersupporting
confidence: 75%
“…Furthermore, the HP [1- 13 C] pyruvate MRSI study after 2 months of treatment with taxane + platinum chemotherapy showed the efficacy of treatment with a reduced k PL value of 0.015 (s −1 ). This clinical study supports the feasibility of HP [1- 13 C] pyruvate MRSI in future clinical studies of metastatic cancer [ 62 , 63 ].…”
Section: Liver Cancersupporting
confidence: 75%
“…In comparison with hyperpolarized 13 C MRI that offers high 13 C signal enhancement of orders of magnitude beyond the Boltzmann polarization and thus allowing to image hyperpolarized 13 C lactate dynamics in vivo, 47 DMI suffers from low signal magnitude, limiting its capability of probing dynamic imaging of 2 H lactate with high spatial resolution. From this point of view, in vivo imaging by hyperpolarized 13 C 48,49 may be superior to DMI for studying glycolysis quantitatively in liver tumors, providing insights into tumorigenesis and malignancy 50 . On the other hand, because of the short window of detection, hyperpolarized 13 C MRI fails to capture downstream metabolites produced from oxidative pathways, that is, H 2 O from the TCA cycle, which is critical in pathological circumstances; however, this is achievable by DMI.…”
Section: Discussionmentioning
confidence: 99%
“…From this point of view, in vivo imaging by hyperpolarized 13 C 48,49 may be superior to DMI for studying glycolysis quantitatively in liver tumors, providing insights into tumorigenesis and malignancy. 50 On the other hand, because of the short window of detection, hyperpolarized 13 C MRI fails to capture downstream metabolites produced from oxidative pathways, that is, H 2 O from the TCA cycle, which is critical in pathological circumstances; however, this is achievable by DMI. Taken together, future studies would likely benefit from utilizing these complimentary techniques together to more deeply characterize metabolic flux.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the liver is a highly metabolic organ, displaying the highest rates of pyruvate-to-lactate and pyruvate-to-alanine conversion among intra-abdominal solid organs [ 46 ]. The use of HP 13 C-MRI to study liver parenchymal diseases, including hepatic steatosis, fibrosis, and malignancies, is presently undergoing thorough investigation [ 58 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%